Evaporation Characteristics of Ethanol Blended Biodiesel Fuel for Generators - Haoxiang WEI; Xiaorong WANG; Genzhu JIANG; Chenjun HUANG; Mingrui ZHANG (南方能源建设)
[Introduction] In the current context of increasing energy demand and environmental conservation advocacy, it is necessary to seek alternative energy sources for traditional fuel generators, and better fuels can be identify by studying the evaporation characteristics of fuels. [Method] The droplet suspension experiments were conducted to investigate the evaporation characteristics of droplets of methyl oleate fuel with ethanol contents of 0%, 20%, 30%, and 50% at the ambient temperature of 673 K and 773 K. [Results] The results indicate that as the ambient temperature increases from 673 K to 773 K, the evaporation rate of the blended droplets rises. Furthermore, with the continuous increase in ethanol contents, the difference in droplet evaporation rates between the two ambient temperatures becomes more pronounced. At lower ambient temperatures, the evaporation process of the droplets is relatively stable, with the droplet evaporation rate showing a gradual decrease trend. The addition of ethanol leads to an extension of the droplet's equilibrium evaporation stage, increasing the evaporation time and inhibiting the evaporation process. Conversely, at higher ambient temperatures, the evaporation process exhibits greater fluctuations, with the droplet evaporation rate showing a gradual increase trend and reaching its maximum at the ethanol content of 50%. The addition of ethanol induces micro-explosion events, reducing the evaporation time and enhancing the evaporation process. Moreover, increasing the ambient temperature and ethanol content promotes the occurrence, intensity, and frequency of micro-explosion events in droplets. [Conclusions] Based on the experimental results of droplet suspension experiments on the evaporation characteristics of methyl oleate and ethanol blended droplets, this study provides important data support and references for related fuel research and applications.